2022
DOI: 10.1021/acsbiomaterials.1c01393
|View full text |Cite
|
Sign up to set email alerts
|

Strontium-Containing Barium Titanate-Modified Titanium for Enhancement of Osteointegration

Abstract: One of the major challenges for Ti-based implants is insufficient osteointegration, which might result in the loosening of the implant. In this study, we fabricated strontium (Sr)-containing barium titanate (BST) on the surface of Ti to improve the bioactivity for osteointegration enhancement. The introduction of Sr significantly reduced the crystallization time and improved crystallinity, which was proved by X-ray diffraction, X-ray photoelectron spectroscopy, and transmission electron microscopy. Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The MT-Sr coating prepared by micro-arc oxidation in this study exhibited a porous surface structure, and more importantly, strontium was introduced into the coating during the micro-arc oxidation process. Research showed that strontium induced MC3T3-E1 cells to differentiate into osteoblasts, which enables proliferation of the osteoblasts, and inhibits the proliferation of osteoclasts and bone absorption, so strontium plays an important role in the process of bone formation (Zhou et al, 2022). The results of this study showed that on the first day after cell inoculation on the material surface, the amounts of cells adhered to the surfaces of each group of samples were different.…”
Section: Discussionmentioning
confidence: 73%
“…The MT-Sr coating prepared by micro-arc oxidation in this study exhibited a porous surface structure, and more importantly, strontium was introduced into the coating during the micro-arc oxidation process. Research showed that strontium induced MC3T3-E1 cells to differentiate into osteoblasts, which enables proliferation of the osteoblasts, and inhibits the proliferation of osteoclasts and bone absorption, so strontium plays an important role in the process of bone formation (Zhou et al, 2022). The results of this study showed that on the first day after cell inoculation on the material surface, the amounts of cells adhered to the surfaces of each group of samples were different.…”
Section: Discussionmentioning
confidence: 73%
“…3a, the diffraction peaks at 22.2°, 31.4°, 38.9°, 45.3°, 51.0°, 56.2°, 66.1°, 70.4° and 75.1° were in agreement with the (100), (110), (111), (002)/(200), (210), (211), (220), (212) and (310) crystal planes of BTO. 29 Among them, a split peak could be observed at around 45°, which is the characteristic peak of tetragonal piezoelectric BTO. 30 All the above peaks match well with the PDF card (JCPDS data No.…”
Section: Resultsmentioning
confidence: 99%
“…3a, the 210), ( 211), ( 220), ( 212) and (310) crystal planes of BTO. 29 Among them, a split peak could be observed at around 45°, which is the characteristic peak of tetragonal piezoelectric BTO. 30 All the above peaks match well with the PDF card (JCPDS data No.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Zhou et al . [239] described the formation of barium titanate films, which were subsequently doped with strontium (Sr) ions, for improved bioactivity for osseointegration enhancement; Sr has been shown to activate various signalling pathways in osteoblasts and osteoclasts, such as the calcium-sensing receptor, inositol 1,4,5 triphosphate, MAPK-ERK1/2 and Wnt/NFATc, enabling bone stem cell osteogenic differentiation and inhibiting osteoclast activity. Due to Sr and Ba having similar ionic radii (1.12 and 1.34 Å, respectively [240]) and electronic structures, substituting Sr into the barium titanate structure is a logical step to not only modify the piezoelectric properties of barium titanate, but to also improve the bioactivity.…”
Section: Modifiable Titanate Structures Based On Ion-exchangeability ...mentioning
confidence: 99%